Mandatory Bequests for Non-Muslim Adopted Children and Stepchildren Perspective of Indonesian Islamic Law - Erna Mastiningrum; Mai Renza Faradilla; Khalista Erlina Najwah (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2025)
A Compilation of Islamic Law in Indonesia includes wasiat wajibah for grandchildren whose parents die and are covered by uncles, like in other Muslim countries. Wasiat wajibah provided for in Article 209 are intended for adopted children and adoptive parents. The development of wasiat wajibah in Indonesia has been greatly advanced through the breakthroughs of the legal judge Ijtihad. Not only for adopted children and adoptive parents, wasiat wajibah in Indonesia are also given to non-Muslim children and non-Muslim families through a decision at the Cassation level as a reference. At present, a broader discussion of the object of giving a will must recur. The discussion concerned the granting of wasiat wajibah to stepchildren, although this was still a matter of pros and cons among mujtahids, in this case, the panel of judges. This type of research is library research with descriptive analytic methods. The object of the research study is Article 209 of the Compilation of Islamic Law and several wasiat wajibah of non-Muslims and stepchildren. This research uses a sociological normative perspective. The purpose of this research is to examine the legal formulation of the wasiat wajibah testament in Indonesia, including Article 209 of the Compilation of Islamic Law, the jurisprudence of wasiat wajibah, and its development.